Preclinical studies of a PARP-targeted theranostic radiopharmaceutical for pancreatic cancer - Gao, Jie; Wang, Yuhao; Wang, Ruoqi; Liu, Mengya; Wang, Hongliang; Li, Jianguo; Du, Jin (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to improve the biodistribution of probes and enhance tumor targeting through 68Ga/177Lu-labeled optimized probes, thereby providing better tumor detection and assessment in PET imaging while also exploring their therapeutic effects on tumors.MethodsThe physicochemical properties of PARPi probes were optimized through polyethylene glycol (PEG) modification. The tumor inhibition effect of the novel probes was validated through the assessment of in vitro affinity, uptake, in vivo distribution, and tumor targeting of the PARPi probes. Based on the distribution results, OLINDA/EXM radiation dose estimation was then performed to optimize the clinically administered dose.ResultsIn the study, a novel PARP-targeted imaging agent, DOTA-PEG-PARPi, was designed and optimized, demonstrating sufficient in vivo stability. The results of in vitro trials showed strong affinity and uptake of PEG-PARPi in pancreatic cancer tumor cells. SPECT/CT imaging revealed significant radioactive accumulation, notable uptake, and prolonged retention time in PSN-1 tumors. Tissue distribution results showed that tumor uptake peaked 3 h after administration. According to dose estimation, the highest absorbed dose was observed in the pancreas of female adults.ConclusionThe PEG-modified PARPi probe not only retained high affinity and targeting capability but also significantly improved retention time during in vivo trials.